Subsurface Geology and Hydrothermal Alteration of The “X” Geothermal Field, West Java: A Progress Report - Peter Pratistha Utama; Pri Utami; Gayatri Indah Marliyani; Randy Wijaya Atmaja (Journal of Applied Geology, 2021)
“X” geothermal field is one of the geothermal fields in West Java. PT. Y (Persero) developed it since 2014. The geothermal field has produced electricity, with installed capacity amounted to 55 MWe. The “X” geothermal system is vapor-dominated. The geothermal manifestations are located at approximately 2,100 m asl. The “X” field consists of three main upflow zones: Kawah Putih, Kawah Ciwidey, and Kawah Cibuni. This study analyzed the drill cuttings from 3 wells as the primary data with total depths ranging from 1,581 to 2,166 m with the well’s highest stable temperatures measured of ±230°C. The three wells selected for this research—Well A, Well B, and Well C—were analyzed to describe the rock properties and estimate the prospect areas of present-day geothermal exploration in the “X” geothermal field.The paper aims to understand better of the subsurface geology and its correlation to the dynamic processes (i.e., hydrothermal alteration) in the “X” geothermal field. The hydrothermal minerals are formed by near-neutral pH fluids and are characterized by quartz, calcite, clays (smectite, illite, chlorite), wairakite, epidote, and actinolite. Acidic fluids are evident by forming acidic hydrothermal mineral, e.g., anhydrite at various depths of the studied wells, particularly at Well C which is located around Sugihmukti-Urug area. Moreover, the previous studies by Reyes (1990), Layman and Soemarinda (2003), Rachmawati et al. (2016), Elfina (2017) on hydrothermal minerals, geothermal manifestation characteristics, fluid geochemistry, and conceptual model are adapted to improve the analysis and interpretation of this paper.